Brazil nut tree: the challenges of extractivism for agricultural plantations - Homma, Alfredo Kingo Oyama; Menezes, Antônio José Elias Amorim de; Maués, Marcia Motta (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
We attempt to describe the historical trajectory of the Brazil nut as a product obtained essentially through gathering, and by the very earliest of Amerindian societies. Despite being an established product in both domestic and foreign markets, Brazil nut trees have suffered from the negative consequences of a series of public policies in the Amazon region. Japanese immigrants who settled in Tomé-Açu (1929) and Parintins (1931) were the first to try planting Brazil nut trees in agroforestry systems (AFS). In the 1980s, with the development of seedlings techniques and grafting by EMBRAPA Amazônia Oriental, large-scale plantations were attempted which struggled to achieve economic viability. The loss of Brazilian hegemony to Bolivia, the changes in the marketing process and the difficulties establishing the Brazil nut as a cultivated plant remain major challenges for the future. The inclusion of Brazil nut trees in agroforestry systems potentially offers one of the most promising ways to ensure their economic viability.